Cintāmaṇiviṣaya pariśōdhanamu : sānubandhamu - China Sitarama Sastri, Vajjhala, 1878- (SAMP early 20th-century Indian books project, 1937)
Study on Āndhraśabdacintāmaṇi, ancient work on Telugu grammar, by Nannaya, 11th cent.